2012
DOI: 10.1007/s12975-012-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

GPER1/GPR30 Activation Improves Neuronal Survival Following Global Cerebral Ischemia Induced by Cardiac Arrest in Mice

Abstract: Female sex steroids, particularly estrogens, contribute to the sexually dimorphic response observed in cerebral ischemic outcome, with females being relatively protected compared to males. Using a mouse model of cardiac arrest and cardiopulmonary resuscitation (CA/CPR), we previously demonstrated that estrogen neuroprotection is mediated in part by the estrogen receptor β, with no involvement of estrogen receptor α. In this study we examined the neuroprotective effect of the novel estrogen receptor, G-protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 29 publications
4
39
0
1
Order By: Relevance
“…The neuroprotective effect of G1 agonist in our study agrees well with the results of previous studies by other investigators [34, 42]. However, our study extends these observations by demonstrating the rapid signaling effects of G1 on activation of the prosurvival kinases, Akt and ERK, and upon inhibition of the proapototic signaling kinase, JNK in the hippocampal CA1 region after GCI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The neuroprotective effect of G1 agonist in our study agrees well with the results of previous studies by other investigators [34, 42]. However, our study extends these observations by demonstrating the rapid signaling effects of G1 on activation of the prosurvival kinases, Akt and ERK, and upon inhibition of the proapototic signaling kinase, JNK in the hippocampal CA1 region after GCI.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies had used a GPR30 agonist (G1) to show that activation of GPR30 could be neuroprotective against GCI [34, 42]. While these studies provided important information that exogenous G1 activation of GPR30 is neuroprotective, the studies had a limitation in that they were not designed to address whether endogenous GPR30 actually mediates the neuroprotective effects of E2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPR30 is involved in protection from ischemia-reperfusion injury in neurons[26], [32] and in cardiomyocytes [33],[34]. Work in chronic kidney disease models has suggested that GPR30 agonists exert protective effects [35].…”
Section: Discussionmentioning
confidence: 99%
“…The behaviors assessed included consciousness (0–3), interaction (0–2), ability to grab a wire top (0–2), motor function (0–5), and activity (0–2). Scores in each category were summated to generate an overall health assessment score (Allen et al, 2011, Kosaka et al, 2012). …”
Section: Methodsmentioning
confidence: 99%